1978
DOI: 10.1901/jeab.1978.30-107
|View full text |Cite
|
Sign up to set email alerts
|

Contrast and Autoshaping in Multiple Schedules Varying Reinforcer Rate and Duration

Abstract: Thirteen master pigeons were exposed to multiple schedules in which reinforcement frequency (Experiment I) or duration (Experiment II) was varied. In Phases 1 and 3 of Experiment I, the values of the first and second components' random-interval schedules were 33 and 99 seconds, respectively. In Phase 2, these values were 99 seconds for both components. In Experiment II, a random-interval 33-second schedule was associated with each component. During Phases 1 and 3, the first and second components had hopper dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Hamilton In fairness to Hamilton and Silberberg (1978), their definition of behavioral contrast is consistent with much of the literature. It is even consistent with much of Rachlin (1973), which implicitly used each of the two definitions in different places.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Hamilton In fairness to Hamilton and Silberberg (1978), their definition of behavioral contrast is consistent with much of the literature. It is even consistent with much of Rachlin (1973), which implicitly used each of the two definitions in different places.…”
supporting
confidence: 53%
“…According to one, interschedule, definition (e.g., Hamilton & Silberberg, 1978) min extinction (ext), mult VI 2-min VI 2-min, mult VI 2-min VI 30-sec, and mult VI 2-min VI 2-min. Positive contrast would occur if the rate of responding emitted during the constant, VI 2-min, component increased when subjects moved from the mult VI 2-min VI 2-min to the mult VI 2-min ext schedule, or from the mult VI 2-min VI 30-sec schedule to the final mult VI 2-min VI 2-min schedule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported just the opposite type of local-rate gradient, as response rates increased throughout the higher valued component and decreased throughout the lower valued component (Buck, Rothstein, & Williams, 1975;Hamilton & Silberberg, 1978;Williams, 1974Williams, , 1976aWilliams, , 1976b. In still other studies, the latter gradients have occasionally occurred in combination with evidence for local contrast, such that a brief elevation at the beginning of the higher valued component was followed by a decrease in rate and then a subsequent increase, thus producing a U-shaped gradient (Williams, 1982; also see Figure 6 of Williams, 1983).…”
mentioning
confidence: 96%
“…In the present experiment, there were no scheduled consequences of signal-key responding. Given the generallyunstable nature of stimulus-directed responding in the topographical tagging procedure (Schwartz, Hamilton, & Silberberg, 1975) and multiple variable-time schedules (Garnzu & Schwartz, 1973;Hamilton & Silberberg, 1978), feedback may constitute an important source of stimulus control. Proprioceptive feedback is thought to control responding separated by short interresponse times (IRTs) in single-stimulus training, and dimensional control of short IRTs is thereby weak (Blough, 1969).…”
Section: Degrees Of Line-tiltmentioning
confidence: 99%